Me, Myself, and A.I.: Should Kenya’s Patent Law Be Amended to Recognise Machine Learning Systems as Inventors? (Strathmore Law Review, 2023)
On 28 July 2021, South Africa set the record for being the first country in the world to grant a patent to an artificial intelligence (AI) system known as ‘Device for the Autonomous Bootstrapping of Unified Sentience’ (DABUS). Although DABUS is not the first AI system to produce patentable products, it is the first AI system to be listed as an inventor in a patent application, attracting worldwide interest. Against this backdrop, this article seeks to analyse whether Kenya’s Industrial Property Act, 2001 (IPA) should evolve to recognise machine learning (ML) systems as inventors. It submits that some ML systems are capable of inventive activity that is equivalent to or superior to that of the human intellect and that such systems should be recognised as inventors. This paper illustrates that Kenya's IPA, however, is unable to recognise ML systems since it is based on anthropocentric standards that, when put into practice, preclude the acknowledgement of non-human inventors. Therefore, this article makes several recommendations aimed at overhauling not only Kenya's IPA but also the country’s patent system.